Absence of linkage between idiopathic dilated cardiomyopathy and candidate genes involved in the immune function in a large Italian pedigree. Issue 10 (October 1994) - Krajinovic, M; Mestroni, L; Severini, G M; Pinamonti, B; Camerini, F; Falaschi, A; Giacca, M
Abstract : Idiopathic dilated cardiomyopathy (IDC) is a heart disease of unknown aetiology characterised by impaired ventricular function usually associated with dilatation of the cardiac chambers. In order to test the hypothesis of an immunological cause for the disease at the genetic level, we performed linkage analysis between the putative disease locus and some of the potential candidate genes involved in the immune response or coding for the targets for autoantibodies in a large multigeneration family (63 members) from southern Italy with autosomal dominant transmission of the disease. Twenty-nine polymorphic markers on 18 different chromosomal locations were investigated, including markers linked to the genes coding for the HLA antigens, the immunoglobulin heavy and light chains, the receptors for the immunoglobulin Fc fragments, the subunits of the T cell receptor and the associated CD3, CD4, CD8, and CD45 antigens, interleukins 1, 3, 4, 5, 6, 9, and 11, the interleukin 1 and 2 receptors, and the genes coding for the beta 1 adrenoreceptor, the adenine nucleotide translocator-1, and the cardiac alpha and beta myosin heavy chains. No evidence for genetic linkage to IDC was found at any of these candidate loci. These results indicate that the still unidentified IDC gene maps outside several loci involved in the regulation of immune reactivity.